Het dagboek en alba amicorum van Sámuel Cseh-Szombathy - Bozzay, Réka (Acta Neerlandica, 2023)
In this paper I have analysed the itinerary of Sámuel Cseh-Szombathy, a former studentof the Reformed College of Debrecen. After having finished his studies in Göttingen andVienna, he started with a journey in 1790 through Southern German cities, the DutchRepublic, England and finally France. During his journey he wrote an itinerary where hemade a record of his costs and what he as a medical doctor found interesting: hospitals,madhouses, natural history collections and of course the most important medicalpersonalities of his time. My main questions are: How unique is this itinerary and howwell does it fit in the Hungarian tradition of itineraries of the Early Modern Time?